Help please
Which of the following reasons would justify Statement 4?
Help please Which of the following reasons would justify Statement - 1

Answers

Answer 1
Answer: The following reasons aren’t stated, but the congruency law is AAS

Related Questions

For the function y = x + 4, what is the output value if 3 is the input value?y = 1 y = 7 y = 12 y = 34
WILL GIVE BRAINLIESTHannah and Han are each trying to solve the equation x² – 8x + 26 = 0. They know thatx = -1 are i& - i, but they are not sure how to use this information to solve for x in theirequation.Part 1- Here is Hannah's work:x? - 8x + 26 = 0X? – 8x = -26Show Hannah howto finish her work using completing the square and complex numbers.Part 2- Han decides to solve the equation using the quadraticformula. Here is the beginning of hiswork-b+V62-4ac-(-8)+7-8)2–401|(26)Finish using the quadratic formula. Simplify the final answer as much as possible.
If I work then I earn money, but if I'm idle, then I enjoy myself. Either I work or I'm idle. However, if I work, then I do not enjoy myself, while if I'm idle, then I do not earn money. Therefore,(a) I work if and only if I enjoy myself(b) I work if I earn money(c) I do not earn money if I'm idle(d) I enjoy myself if and only if I do not earn money
❌❌EVALUATE SQUARE ROOTS❌❌1. Evaluate 6 + √14 + x - √9x when x = 2. a) 10 - 3√2 b) 10 - √2 c) 7 d) -4 2. Evaluate 6 + √14 + x - √9x when x = 2. (Write as decimal) a) 14.24 b) 7 c) 5.76 d) -4 Thank you !
If y=2x-3 were changed to y=2x+5 , how would the graph of new function compare with the original?

What is the length of the longer side in this triangle

Answers


Did you notice the little box with corners marked in the angle down at the bottom ?
That angle is a right angle, and this triangle is a right triangle !

This piece of information is a big help.  It breaks the problem wide open.
You know that in order to find the longest side of a right triangle . . .

-- Square the length of one short side.
-- Square the length of the other short side.
-- Add the two squares together.
-- Take the square root of the sum.

One short side=48.           Its square = 2,304.
The other short side=48.  Its square = 2,304.
Add the two squares:        2,304 + 2,304 = 4,608

The square root of the sum = √4,608 = 67.88 (rounded)


can you write an equation by setting an expression equal to itself. would an equation like this be true

Answers


Of course !  An expression is always equal to itself.

But if there's, say, an 'x' in the expression, then such an equation would be true
for x=every possible number.  You might say it has an infinite number of solutions ...
which certainly has to be true, because no matter what you do to an expression,
it's still always equal to itself !

 
yes it would be as long as it truly equals eachother

A direct variation function contains the points (–8, –6) and (12, 9). Which equation represents the function? y = –x

Answers

you multiply by using the formula

x1*x2=y1*y2

Three lights go on together first changes every 5 sec second every 6sec third every 8 sec when is the next time they go on together

Answers

In order to calculate, you need to find their LCM
LCM of 5,6 and 8 is equal to 120

So, That time will be 120 sec = 2 min.
In short, Your Final Answer would be 2 min.

Hope this helps!

F (t) = 2t - 3 f (7)

Answers

Answer:

11

Step-by-step explanation:

Here the given function, f(t)=2t-3 By substituting t = 7 in the above equation, We get, (7)=2\times 7-3  =14-3   ( By multiplication )

=11  ( By subtraction ) Hence, the value of f(7) is 11 for the given function.

PLEASE I NEED HELP!!!!!!!!! Which expressions are equivalent to 2x - 4 + 4(3x - 2) Select EACH correct answer. A. 4(5x - 2) B.2(7x - 6) C. 8x(3x - 6) D.2x - 8(3x - 2) E.14x - 12

Answers

 C. 8x(3x - 6)
im 100% right
2x-4+4(3x-2)
2x-4+12x-8 (open the brackets)
2x+12x-4-8
14x-12
2(7x-6) (factorize it)
the correct answer is B